PENGEMBANGAN E-MODUL BERBASIS INKUIRI TERBIMBING TERINTEGRASI NILAI-NILAI KARAKTER PADA MATERI SISTEM PENCERNAAN MANUSIA KELAS XI - Eva Oktaviana; Triana Asih; Handoko Santoso (EDUBIOLOCK, 2022)
This development research aims to produce teaching material products in the form of guided..inquiry-based e-modules integrated with character values ​​in human digestive system materials that are suitable for use. The development of this e-module uses a 4-D model, covering four stages, namely, Define (analyze needs), Design (design e-module products), Develop (develop designed e-module products), and Disseminate (Product deployment). The instrument used is an assessment questionnaire. There are two types of questionnaires used, namely the first expert validation questionnaire with 2 assessments (material and design). Both student response questionnaires. The e-module is validated by design and material experts, both validators provide suggestions and comments to improve the e-module. Products that have been revised on the advice of design experts get an average percentage score of 95% and material experts get an average..percentage score of 91%. The e-module product was tested in Class XI IPA SMA Muhammadiyah 2 Metro. Getting a score of all aspects getting a percentage of 89%. The results of expert validation and student responses show that the e-module developed is "Very Appropriate". So that it can be used by students and teachers in the online and offline learning process. This development research has limitations, namely in the stage of spreading it on a small scale.